2012
DOI: 10.1007/s11258-012-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

Seedling emergence and establishment of Pinus sylvestris in the Mongolian forest-steppe ecotone

Abstract: The potential of Scots pine (Pinus sylvestris) for regeneration and encroachment onto dry grasslands in the forest-steppe ecotone was experimentally studied at the south-eastern distribution limit of the species in Mongolia. The experiment consisted of a sowing and planting (2-year old seedlings) assay at two different distances from the forest line and manipulation of the water supply by irrigation in one half of the replicate plots. Seedling emergence was strongly inhibited by post-dispersal seed predation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…During dry years, however, larger pine trees exhibited stronger growth reductions (Zang et al, 2012). Studies on the regeneration of Scots pine and encroachment onto the steppe at the forest-steppe ecotone in northern Mongolia revealed that the distribution of this species was very limited, and was mostly restricted to the immediate vicinity of the forest (Dulamsuren et al, 2013). Eilmann et al (2011) concluded that Scots pine trees under drought stress build a more effective water-conducting system (larger tracheids).…”
Section: Vulnerability Of Pine Forests To Drought In the Forest-steppmentioning
confidence: 99%
“…During dry years, however, larger pine trees exhibited stronger growth reductions (Zang et al, 2012). Studies on the regeneration of Scots pine and encroachment onto the steppe at the forest-steppe ecotone in northern Mongolia revealed that the distribution of this species was very limited, and was mostly restricted to the immediate vicinity of the forest (Dulamsuren et al, 2013). Eilmann et al (2011) concluded that Scots pine trees under drought stress build a more effective water-conducting system (larger tracheids).…”
Section: Vulnerability Of Pine Forests To Drought In the Forest-steppmentioning
confidence: 99%
“…In arid and semi‐arid forests and woodlands, cool, wet climatic conditions have historically been optimal for regional tree recruitment events (League & Veblen, ; Barger et al ., ; Shinneman & Baker, ). Experimental temperature and water manipulations further confirm the negative effects of increasing water deficits on tree recruitment (McCallum, ; Dulamsuren et al ., ). While these previous studies suggest that regional warming may alter forest and woodland composition and structure in many semi‐arid ecosystems, warming effects may vary depending on differences in local climate, soil properties, and vegetation structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, in years with good seed production (mast years), seed consumption by granivores does not threaten forest regeneration. On the other hand, in cases of low seed production, small mammals may consume all seeds on the ground, and natural regeneration may outright fail as a result (see Sukachev and Dylis 1964 ;Castro et al 1999 ;Dulamsuren et al 2013 ).…”
Section: Mammalsmentioning
confidence: 99%
“…Seed removal by seed predators was also the main reason for failure of Scots pine seedling emergence in the Mongolian forest steppe. In the forest steppe, 66-92 % of the seeds were lost to seed predators, while 52-76 % were removed at the forest edge (Dulamsuren et al 2013 ).…”
Section: Mammalsmentioning
confidence: 99%